Stages of Development of the Stock Market of Uzbekistan - Sultonali Umaraliyevich, Mekhmonov; Utkur Azimovich, Abdullaev; Isroil Ibrokhimovich, Juraev; Khabibullokh Ravshan Ugli, Razzokov (International Journal of Psychosocial Rehabilitation, 2020)
This article details in detail the stages of development of the stock market of the Republic of Uzbekistan and the effective work in this direction, the important decisions of the president of the country,.